The Strategi Kepala SD-LB dalam Meningkatkan Kinerja Guru - Vivid Agus Tridora; Kms Badaruddin; Amilda Amilda (Program Magister Manajemen Pendidikan Islam Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2021)
This study aims to identify, describe and analyze and provide alternative solutions to the factors supporting and inhibiting the principal's strategy in improving teacher performance at SD-LB Bina Autis Mandiri (BAM). This research uses a case study research type by design because the researchers look at cases, events and everyday events at Bina Autism Mandiri as the ones that will be used as research. The results of this study are the strategy used by the principal in improving teacher performance at SD-LBBina Autis Mandiri Palembang, namely conducting a strict selection of teachers through academic tests and also medical debriefing. Applying democratic leadership by accepting criticism, suggestions from every effective teacher for the learning process, providing persuasive training to teachers, also using individual approach strategies for teachers to be fostered and directed directly in an effort to improve the teacher's strategy. Teacher performance is quite good through teacher competency assessment. Inaddition, teacher performance is measured through evaluation results from the supervision of the principal. Supporting factors are teachers who have ideas and creativity in managing the learning process, school facilities and persuasive training for teachers, democratic attitudes of school principals, and awarding rewards for teachers. While the inhibiting factors come from the teacher's internal factors, the age of the teacher who has difficulty understanding technology media, the teacher's personal problems that are carried over to teaching and learning activities and have an impact on the lack of concentration in the classroom.